Georgian - Icelandic Literary Relations - Michaela Krejčová (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
What are the literary relations between two small countries, like Georgia and Iceland, which are very far one from each other, with very different languages, cultures and histories? Despite the great distance and the differences between those two cultures, some literary contacts between Georgia and Iceland exist. Although my research shows that the literary contacts started first in the 20th century, numerous works have been translated. This article is focused on the literary relations between Georgia and Iceland in the fields of translation of literary fiction and the reception of those translations in both countries.